Uric Acid Determination in Gestational Hypertension: Is it as Effective a Delineator of Risk as Proteinuria in High-Risk Women?. (October 2015) - Schmella, Mandy J.; Clifton, Rebecca G.; Althouse, Andrew D.; Roberts, James M.
We asked, is uric acid as effective as proteinuria at identifying perinatal risk in high-risk women with gestational hypertension? Uric acid was measured in samples obtained ≈4.6 weeks predelivery in 259 women with prior preeclampsia from the National Institute of Child Health and Human Development network study of low-dose aspirin to prevent preeclampsia. Participants were grouped according to the presence/absence of gestational hypertension (H), proteinuria (P), and hyperuricemia (U). Adverse perinatal outcomes were not different between H or U and women with normal values (normal blood pressure, urinary protein, and uric acid [NNN]). Preterm birth was greater in hypertension and proteinuria (HP) and hypertension and hyperuricemia (HU) compared to NNN (relative risk [RR] = 2.4, P = .03 and 3.8, P < .01), respectively. In addition, in HU women, delivery was earlier (36.6 ± 3.4 vs 38.4 ± 2.3 weeks, P < .001) and small for gestational age infants <fifth centile more frequent (RR = 8.2, P = .01) compared to NNN women. This study sought to determine if uric acid is as effective as proteinuria at identifying perinatal risk in high-risk women with gestational hypertension. Our results suggest that hyperuricemia is at least as accurate as proteinuria at identifying perinatal risk in high-risk women with gestational hypertension.